Socio-Economic Factors Influencing the Conservation of Cherang’any Forest in Elgeyo-Marakwet County, Kenya - Mang’ira, Solomon K.; Koske, James K.; Kerich, Richard K. (African Journal of Education,Science and Technology (AJEST), 2023)
Globally, forests make up an approximately 30% of the world’s total land area with an estimated 11% being traditionally managed production landscapes. Presently, Kenya forest cover is about 7.5% which is significantly smaller than the desired minimum of 10.0% land areas. Forest ecosystems face significant challenge from a combination of human – ecological factors arising from the confluence between the andropological and environmental factors. Due to the depletion in the forest cover in Kenya, the study examined the various socio-economic factors influencing the conservation of Cherang’any forest, Elgeiyo-Marakwet County, Kenya. The study targeted 343 individuals from 343 households from which 300 individuals were randomly sampled from the boundaries of the forest zone and purposively sampled 43 key informants. The study instruments comprised of observations, interviews and questionnaires. The qualitative data obtained from the study was analyzed thematically and used to develop a questionnaire from which quantitative data was drawn. Based on a Cronbach’s coefficient value ≥ 0.70, the questionnaire was considered reliable. The findings indicated that socio-political factors that are largely related to the historical colonial legacy of protectionist environmental policies have largely influenced the current conservation policy and this has led to communal conflict and ethnic identification with conservation. The study recommends that the Forest Conservation and Management Act of 2016 of Kenya, should help the Sengwer community in the establishment of Community Forest Associations. The research recommended a further inquiry into the influence of socio-economic variables on the low sense of forest ownership and management among local communities in Kenya.